An epidemiologic investigation of injuries affecting young affecting young competitive female gymnasts - Caine, D.; Cochrane, B.; Caine, C.; Zemper, E. (The American Journal of Sports Medicine, 1989)
A prospective study of injuries affecting 50 highly competitive young female gymnasts was conducted over a period of 1 year. Many of the findings of this investigation were consistent with previous studies and suggest particular injury trends in women's gymnastics. These results included injury location, injury severity, nature of onset, event, and activity at the time of injury. Some of the descriptive results, however, provided information that was heretofore unreported or inconsistent with previous investigations. These findings involved injury rate, reinjury rate, time loss, injury type, hours of practice, and incidence of physician-seen injuries. Some of these findings were disturbing and echo concerns registered in the professional literature. In particular, the reinjury rate is alarming and points to the need for complete rehabilitation before return to full participation. The results of the analytic component of the study alluded to the potential role of competitive level and maturation rate in the profile of the injury-prone gymnast. Specifically, rapid periods of growth and advanced levels of training and competition appeared to be related to injury proneness. Pursuant to the descriptive and analytic results of the investigation, recommendations for injury prevention and continued research are made. Source: THE AMERICAN JOURNAL OF SPORTS MEDICINE, 17(6):811-820 (1989)